A biodegradable multifunctional nanofibrous membrane for periodontal tissue regeneration. (May 2020) - Liu, Xuezhe; He, Xi; Jin, Dawei; Wu, Shuting; Wang, Hongsheng; Yin, Meng; Aldalbahi, Ali; El-Newehy, Mohamed; Mo, Xiumei; Wu, Jinglei
Abstract: Biomaterial-based membranes represent a promising therapeutic option for periodontal diseases. Although conventional periodontal membranes function greatly in preventing the ingrowth of both fibroblasts and epithelial cells as well as connective tissues, they are not capable of promoting periodontal tissue regeneration. Here, we report a multifunctional periodontal membrane prepared by electrospinning biodegradable polymers with magnesium oxide nanoparticles (nMgO). nMgO is a light metal-based nanoparticle with high antibacterial capacity and can be fully resorbed in the body. Our results showed that incorporating nMgO into poly(L-lactic acid) (PLA)/gelatin significantly improved the overall properties of membranes, including elevated tensile strength to maintain structural stability and adjusted degradation rate to fit the time window of periodontal regeneration. Acidic degradation products of PLA were neutralized by alkaline ions from nMgO hydrolysis, ameliorating pH microenvironment beneficial for cell proliferation. In vitro studies demonstrated considerable antibacterial and osteogenic properties of nMgO-incorporated membranes that are highly valuable for periodontal regeneration. Further investigations in a rat periodontal defect model revealed that nMgO-incorporated membranes effectively guided periodontal tissue regeneration. Taken together, our data indicate that nMgO-incorporated membranes might be a promising therapeutic option for periodontal regeneration. Statement of Significance: Traditional clinical treatments of periodontal diseases largely focus on the management of the pathologic processes, which cannot effectively regenerate the lost periodontal tissue. GTR, a classic method for periodontal regeneration, has shown promise in clinical practice. However, the current membranes might not fully fulfill the criteria of ideal membranes. Here, we report bioabsorbable nMgO-incorporated nanofibrous membranes prepared by electrospinning to provide an alternative for the clinical practice of GTR. The membranes not only function greatly as physical barriers but also exhibit high antibacterial and osteoinductive properties. We therefore believe that this study will inspire more practice work on the development of effective GTR membranes for periodontal regeneration. Graphical abstract: Image, graphical abstract